Evaluación de la factibilidad del cambio del sistema de Generación eléctrica actual, por un sistema híbrido solar fotovoltaico y GLP en el cluster PS1 (2020)
This study will discuss the challenges to implement a hybrid system, solar Photovoltaic and LPG fuel to offset the constraints on the intermittent energy, reducing GreenHouse Gases (GHG) emissions and power consume costs. Using SOLARGIS the solar software and a matrix to calculate the consumptions of LPG, the results of this study was that using de hybrid system the results obtained were that with the implementation of the hybrid system, it saves 15% of the lifting cost compared to the current diesel generation scenario.